Utilization of waste paper as teaching media for volcano eruption simulation in improving student knowledge - Hamna, H.; Hidayat, Syaiful; Ummah BK, Muh. Khaerul; Rahmawati, Karmila Risa; Rivani, R.; Nurmasayu, Andi; Yago, Ribka; Wahyuni, Ni'mah (Journal of Community Service and Empowerment, 2024)
Indonesia has the highest number of active volcanoes in the world due to its geologic location at the confluence of the Eurasian and Australian plates. However, despite this, the knowledge of local communities regarding volcanic eruptions is still very minimal. Therefore, it is important to provide education to the community in this context is the local community. This Community Service Program aims to increase community knowledge related to the process of volcanic eruption by using pulp-based learning media, so that it can become disaster mitigation knowledge. The methods used are observation, coaching or training based on practical simulations, questionnaires and interviews. The subject of this Community Service is the community of Tambun village, Baolan sub-district, Tolitoli district, totaling 21 people in collaboration with students of the elementary school teacher education program in semester III. The results of this program are the increase in community knowledge related to volcanic eruptions and the growth of community awareness related to the use of waste paper, this is in line with SDGs 4 and SDGs 17 relating to quality education and partnerships with the community.